Evaluation of Alternative Methods of Tunnel Composting (submitted by the European Composting Network). (5th August 2020) - ,; Koutsoumanis, Konstantinos; Allende, Ana; Bolton, Declan Joseph; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve Maria; Hilbert, Friederike; Lindqvist, Roland; Nauta, Maarten; et al.
Abstract: Two alternative methods for the production of compost from certain category 3 animal by‐products (catering waste and processed foodstuffs of animal origin) were assessed. The first proposed a minimum temperature of 55°C for 72 h; the second 60°C for 48 h, each with a maximum particle size of 200 mm. The proposed composting processes were assessed by the BIOHAZ Panel for their efficacy to achieve a reduction of 5 log10 of Enterococcus faecalis or Salmonella Senftenberg (775W, H2 S negative) and a 3 log10 reduction of the infectivity titre of thermoresistant viruses, such as parvovirus, in the composted material, as set out in Annex V, Chapter 3, Section 2 of Commission Regulation (EU) No 142/2011. The assessment of the BIOHAZ Panel exclusively focused on the ABP raw materials (catering waste and processed foodstuffs) intended for human consumption. The applicant did not provide any validation experiments with direct measurement of the reduction of viability of endogenous indicators or spiked surrogate bacteria. However, from thermal inactivation parameters reported in the literature, it can be concluded that the proposed composting standards can achieve at least a 5 log10 reduction of Enterococcus faecalis or Salmonella Senftenberg 775W. The applicant did not consider thermoresistant viruses as a relevant hazard and therefore did not provide any data from direct measurements of the reduction of infectivity of spiked thermoresistant viruses, nor provide data from validation studies undertaken at national level or data from literature supporting the efficacy of the proposed composting standards on thermoresistant viruses. However, thermoresistant viruses should be considered to be a relevant hazard in this context and validation data should have been provided accordingly. The BIOHAZ Panel considers that the evidence provided by the applicant does not demonstrate that the requirements of Annex V, Chapter 3, Section 2 of Commission Regulation (EU) No 142/2011 are achieved.